Ketergantungan Impor Dan Posisi Indonesia Dalam Perdagangan Kedelai Internasional - Achmad eka febriansah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the level of Indonesia’s dependence on soybean imports and to identify the factors influencing the national soybean import volume. As a country adhering to an open economic system, Indonesia continues to face a gap between domestic soybean consumption needs and domestic production capacity, making imports the primary solution to close this deficit. This research employs a quantitative approach using multiple linear regression analysis, in which soybean import volume is positioned as the dependent variable, while domestic soybean production, domestic soybean prices, and the exchange rate of the Indonesian Rupiah against the United States Dollar serve as independent variables. The data used are secondary time-series data obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The simultaneous test (F-test) results indicate that the three independent variables jointly have a significant effect on Indonesia’s soybean import volume, with an F-value of 7.856 and a significance level of 0.009. The Adjusted R Square value of 0.652 indicates that 65.2% of the variation in soybean import volume can be explained by the model, while the remaining 34.8% is explained by factors outside the model. Partially, only the domestic soybean production variable is proven to have a negative and significant effect on import volume, meaning that an increase in domestic production can directly reduce import dependency. In contrast, domestic soybean price and the Rupiah–US Dollar exchange rate do not show a statistically significant partial effect. This study concludes that the root cause of Indonesia’s soybean import dependency is structural, namely the inability of domestic production to keep pace with rising consumption, so an integrated strategy to increase production is needed to strengthen national food self-sufficiency. Keywords: soybean imports, domestic production, food dependency, multiple linear regression, international trade